Enhancing Entrepreneurial and Employability Skills through Work-Integrated Learning in Mechanical Technology Education for Achieving SDG 4 in South-South Nigeria - Chiemeke; Kanu (Journal of Research in Industrial Technology and Educational Studies, 2026)
A descriptive survey research design was adopted for this study. The population comprised lecturers and industrial staff from selected universities and industries in Nigeria. A sample of 120 respondents was selected using purposive and simple random sampling techniques. Data were collected using a structured questionnaire titled Work-Integrated Learning and Entrepreneurial Skills Development Questionnaire (WILESDQ). The instrument was validated by experts in Industrial Technology Education and Measurement and Evaluation department, and a reliability coefficient of 0.86 was obtained using Cronbach Alpha.The data collected were analyzed using mean, standard deviation, and t-test statistics. The findings revealed that Work-Integrated Learning (WIL) significantly enhances entrepreneurial and employability skills such as technical competence, problem-solving ability, innovation, and business management skills among students. The study further revealed that increased funding for WIL programmes, training and retraining of lecturers and industrial supervisors, exposure of students to modern technologies and digital tools, provision of modern workshop facilities and equipment, strong collaboration between industries and educational institutions, and regular supervision and monitoring of students during industrial training are important strategies for improving skill acquisition. In addition, periodic review of the curriculum to align with industry needs, as well as organizing workshops, seminars, and industry-based training programmes, were identified as effective strategies for enhancing students’ employability and entrepreneurial skills. The study concluded that strengthening Work-Integrated Learning programmes is essential for improving graduate employability and promoting entrepreneurship development in Nigeria. The study recommends stronger university–industry partnerships, improved funding for technical education, and the integration of entrepreneurship training into Industrial Technology Education curricula.